PRELIMINARY STUDIES OF SYNTHESIS POLYURETHANE MEMBRANE OF NYAMPLUNG SEED OIL (Calophyllum inophyllum) WITH HEXAMETHILENE-1,6-DIISOCYANATE (HMDI) - Mutia Farida; Mustanir Yahya; Marlina Marlina (Jurnal Natural, 2016)
Nyamplung oil originated from Ujong Pancu, Aceh Besar is one of the vegetable oil sources which is not fully utilized yet. The extraction of nyamplung oil is done using soxhletation with n-hexane solvent; during this process, the oils produced is at the 55.55% levels. The product is in the form of yellowish green liquid with the density of 0.88gr/ml. The nyamplung oil extract has the iodine number of iod 83.53 mg iod/g and hydroxyl number of  64.292 mg KOH/gram which can be utilized as the raw material in making polyurethane membrane. Polyurethane membrane is synthesized by reacting fatty acids from nyamplung seed oil with hexamethylene-1.6-diisocyanate (HDMI). The ration of the oil towards HDMI is variated as, 5:1;5:3;5:5;5:7;5:9 v/w. The membrane has a composition of  5:7 v/w  with 90-100 oC polymerization temperatures and  160oC curring temperature for 8 hours is hard, homogenous and quite elastic with a transparent brown colour.